Review on TAS-102 development and its use for metastatic colorectal cancer. (August 2016) - Mota, Jose Mauricio; Fonseca, Leonardo G.; Braghiroli, Maria Ignez; Hoff, Paulo M.
Highlights: Trifluridine, a fluoropyrimidine, had previously had its clinical development halted due to its rapid degradation by thymidine phosphorylase. Combining trifluridine with tipiracil, a thymidine phosphorylase inhibitor, circumvented this issue and enabled further research. Recently, the RECOURSE trial demonstrated TAS-102 as a novel strategy against metastatic colorectal cancer. Abstract: TAS-102 is the combination of trifluridine (TFT) with tipiracil (TPI) in a 1:0.5 molar ratio. TFT is a fluoropyrimidine that retains cytotoxic activity in 5-fluorouracil resistant cell lines. Due to TFT short half-life, early clinical development was discouraging. Thereafter, TFT was shown to be promptly degraded by thymidine phosphorylase, also known as platelet-derived endothelial cell growth factor, a pro-angiogenic protein and a poor prognosis marker in colorectal cancer. TPI is a specific antagonist of thymidine phosphorylase and led to an increase in TFT serum levels when both agents are combined. Moreover, TPI is a potential anti-angiogenic molecule and could exert antitumor actions per se . TAS-102 was tested in several Phase I studies published in the early 21st century. The best regimen was settled as 70 mg/m 2 /day, q12 h, orally given at days 1–5 and days 8–13, each 28 days. Recently, the first Phase III trial evaluating TAS-102 in refractory colorectal cancer patients was published. The RECOURSE trial demonstrated a survival advantage of the agent over supportive care, and definitely established TAS-102 as a novel strategy in the current armamentarium against colorectal cancer. Here we review the preclinical data regarding TFT and TPI that led to the development of TAS-102, and the set of clinical data that ultimately proved that TAS-102 improved outcomes in colorectal cancer patients.